GM1 ganglioside-independent intoxication by Cholera toxin - Cervin, J; Wands, A; Casselbrant, A; Wu, H; Krishnamurthy, S; Cvjetkovic, A; Estellius, J; Dedic, B; Sethi, A; Wallom, K; Rilse, R; Backstrom, M; et al. (Public Library of Science, 2018)
Cholera toxin (CT) enters and intoxicates host cells after binding cell surface receptors via its B subunit (CTB). We have recently shown that in addition to the previously described binding partner ganglioside GM1, CTB binds to fucosylated proteins. Using flow cytometric analysis of primary human jejunal epithelial cells and granulocytes, we now show that CTB binding correlates with expression of the fucosylated Lewis X (LeX) glycan. This binding is competitively blocked by fucosylated oligosaccharides and fucose-binding lectins. CTB binds the LeX glycan in vitro when this moiety is linked to proteins but not to ceramides, and this binding can be blocked by mAb to LeX. Inhibition of glycosphingolipid synthesis or sialylation in GM1-deficient C6 rat glioma cells results in sensitization to CT-mediated intoxication. Finally, CT gavage produces an intact diarrheal response in knockout mice lacking GM1 even after additional reduction of glycosphingolipids. Hence our results show that CT can induce toxicity in the absence of GM1 and support a role for host glycoproteins in CT intoxication. These findings open up new avenues for therapies to block CT action and for design of detoxified enterotoxin-based adjuvants.